Dielectric Properties of Hevea Rubber Latex - Hassan, Jumiah (1999)
The dielectric properties of Hevea Rubber Latex have not been thoroughly investigated and are, therefore, not well understood. It is a biological product with a complex composition. A typical composition of freshly tapped natural rubber is made up of 50-80% water, 18-45% rubber hydrocarbon and 2-5% non-rubber constituents. The basic components of non-rubber constituent are proteins, lipids, quebrachitol and inorganic salts. Measurements of the dielectric properties at various moisture contents and temperature s -20 to -60°C in the lowfrequency region of 10⁻² to 10⁶ Hz were done using the Dielectric Spectrometer. The results of the measurement in the low-frequency region are expressed using the dielectric response model. For Hevea rubber latex, three distinct responses have been indicated. These are the real relative permittivity at high frequency ɛ(∞), the loss peak response ɛip and the conductance G. The total losses are conductive losses which arise due to the conducting phases found in latex, and dipolar losses which appear as loss peak responses due to the relaxation of the water molecules. The relaxation peak is shifted to a higher frequency as water content in the latex decreases and as temperature increases. This phenomenon could be due to the difference in the mechanism of polarisation relating to ion and the polarisation relating to ice. The activation energy for latex concentrate is l.66 eV while for fresh latex 2.34 eV. Ice has a non-constant activation process. This is due to the existence of two activation processes. The first activation process gives an activation energy of 0.51 eV whilst the second activation process results in a much lower activation energy. The high activation energy for fresh latex as compared to ice could be due to latex particles being bonded by the water molecules which needs more energy to dissociate. In the microwave region of 0.2 to 20 GHz, dielectric measurements were done using an open-ended coaxial sensor and an automated network analyser at various moisture contents and temperatures from -30 to 50°C. Experimental results in the microwave region show that in the liquid state a conductive loss due water molecules. However, at 10 GHz there is a good relationship between the dielectric properties of hevea latex and moisture content and is almost unaffected by the non-rubber constituents, presevatives and temperature Therefore, 10 GHz is the most suitable frequency for the analysis and design of the microwave moisture meter or latexometer There is a steep increase in the real relative permIttivity of about one order of magnitude and dielectric loss factor of about two orders as the phase of latex changes from solid to liquid.